Der schmerzende Ellbogen bei Kindern und Jugendlichen im Sport - Vavken, P.; Jensen, J. (sems-journal, 2021)
Abstract Pediatric and adolescent athletes have a high risk for elbow problems. In most cases these problems are due to overuse and can heal if diagnosed in time and treated with avoiding further overload. Traumatic elbow problems are less frequent and because of their often subtle symptoms they are at risk of underdiagnosis. Finally, there are infrequent congenital and idiopathic elbow problems. This article reviews these diagnoses and the basics of their treatment.